ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI MINAT WAJIB PAJAK UNTUK MENGGUNAKAN E-FILING - Pramana, Gede Wira Jaya; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTIn order to maximize the tax revenue, the Directorate General of Tax has conducted administration reformation in the field of taxation. One of the reformation programs is the implementation of e-filing as the reporting facility of the annual tax return of individual income tax, it has been expected that the implementation of e-filing can ease the personal taxpayer in conducting the tax obligation so it will increase the state revenue. This research is meant to analyze the implementation of e-filing system as the reporting facility of annual tax return of Individual Income Tax at KPP Pratama Surabaya Gubeng. The interview has been conducted gradually to the tax officers and personal taxpayers in using e-filing and without e-filing. The result of this research shows that the implementation of e-filing is ineffective; the implementation of e-filing has not been running well and the expected intensity has not been working maximally yet. The cause is there are taxpayers who have not understandand know the way to use the e-filing. The implementation of e-filing will be maximal if the Directorate General of Tax has carried out some improvements and enhancementof servicesand facilities to the taxpayers and it is supported by the rules which oblige the use of e-filing to all personal taxpayersKeywords: tax payers, e-filling, annual tax return.